Pengolahan Air Gambut Menjadi Air Bersih Menggunakan Metode Elektrokoagulasi dan Filtrasi - Mardhatillah, Lady Cleophila; Anriani, Ayuni; Juniarty, Aulia Yahya; Purnaini, Rizki (Jurnal Teknologi Lingkungan Lahan Basah, 2023)
Treating peat water with simple technology to meet clean water standards is a viable solution for addressing community water needs. This study combines electrocoagulation and filtration methods to achieve desired results. Electrocoagulation combines electrochemical processes with flocculation-coagulation, while filtration removes suspended solids through a porous medium. The research demonstrates the method's effectiveness in enhancing peat water quality. It reduces iron levels from 0.27 mg/l to 0.04 mg/l, changes water color from brown to clear white, increases pH from 5.0 to 8.2 (within clean water standards of 6.5-8.5), and lowers TDS from 33.1 mg/l to 10.1 mg/l. The design of this peat water treatment device utilizing electrocoagulation and filtration is remarkably simple, allowing for easy implementation by individuals in their regions. The process is uncomplicated, and required filter media are readily available in the market. These findings provide a practical solution to meet clean water needs by effectively treating abundant peat water sources.